Successful treatment with afatinib after grade 3 hepatotoxicity induced by both gefitinib and erlotinib in EGFR mutation-positive non-small cell lung cancer. (September 2016) - Zenke, Yoshitaka; Umemura, Shigeki; Sugiyama, Eri; Kirita, Keisuke; Matsumoto, Shingo; Yoh, Kiyotaka; Niho, Seiji; Ohmatsu, Hironobu; Goto, Koichi
Highlights: We describe a case of grade 3 hepatotoxicity induced by both gefitinib and erlotinib. The patient had the UGT1A1 and CYP3A5 poor metabolizer phenotypes. Afatinib, which is not metabolized by CYP-related enzymes, successfully treated the tumor. Evaluation of SNPs in metabolic enzymes may predict EGFR -TKI-induced hepatotoxicity. Abstract: Hepatotoxicity is a major cause of the withdrawal of epidermal growth factor receptor tyrosine kinase inhibitors ( EGFR -TKIs) when treating EGFR mutation-positive non-small cell lung cancer (NSCLC). We report a case in which gefitinib- and elrotinib-induced severe hepatotoxicity arose in a patient with the uridine diphosphate glucuronosyltransferase isoform 1A1 (UGT1A1) and cytochrome p450 3A5 (CYP3A5) poor metabolizer phenotypes. Afatinib is not significantly metabolized by cytochrome p450-mediated pathways. We describe successful management of the patient's tumor by switching to afatinib. Evaluation of single nucleotide polymorphisms (SNPs) in metabolic enzymes might be useful to predict severe hepatotoxicity induced by EGFR -TKIs.